2021
DOI: 10.1111/nph.17258
|View full text |Cite
|
Sign up to set email alerts
|

Vertical decoupling of soil nutrients and water under climate warming reduces plant cumulative nutrient uptake, water‐use efficiency and productivity

Abstract: Summary Warming‐induced desiccation of the fertile topsoil layer could lead to decreased nutrient diffusion, mobility, mineralization and uptake by roots. Increased vertical decoupling between nutrients in topsoil and water availability in subsoil/bedrock layers under warming could thereby reduce cumulative nutrient uptake over the growing season. We used a Mediterranean semiarid shrubland as model system to assess the impacts of warming‐induced topsoil desiccation on plant water‐ and nutrient‐use patterns. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 105 publications
4
55
1
Order By: Relevance
“…This is evidenced by the frequent positive correlations in D trees between tree-ring δ 18 O and nutrient concentrations (Table 2). Therefore, our results fit well within the conceptual model recently put forward by Querejeta et al [93], who postulated that heavier utilization of subsoil/bedrock water induced by topsoil desiccation leads to deterioration of vegetation mineral nutrition due to the vertical decoupling of water and nutrient availability in soil/bedrock profiles. Differences between vigor classes may arise from the location of D trees on exposed microsites and/or sites with shallow soils with low water-holding capacity, as has been proposed before for N. dombeyi [42] and Mediterranean Quercus species [86,94] undergoing dieback.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is evidenced by the frequent positive correlations in D trees between tree-ring δ 18 O and nutrient concentrations (Table 2). Therefore, our results fit well within the conceptual model recently put forward by Querejeta et al [93], who postulated that heavier utilization of subsoil/bedrock water induced by topsoil desiccation leads to deterioration of vegetation mineral nutrition due to the vertical decoupling of water and nutrient availability in soil/bedrock profiles. Differences between vigor classes may arise from the location of D trees on exposed microsites and/or sites with shallow soils with low water-holding capacity, as has been proposed before for N. dombeyi [42] and Mediterranean Quercus species [86,94] undergoing dieback.…”
Section: Discussionsupporting
confidence: 90%
“…The higher water-use efficiency and lower oxygen isotope composition of dead trees, and the uncoupling of the latter from leaf-level processes, pointed to their increased drought stress and water uptake from deeper soil layers. Considering the vertical decoupling between water and nutrient availability in soil/bedrock layers [93], dead trees experienced a long-term deterioration of nutritional status aggravating hydraulic and growth impairment triggered by successive droughts that could have played a critical role in dieback and mortality processes. In view of the outstanding patterns in Ca and Mn concentrations and related stoichiometric ratios, they may be useful early-warning signals of drought-induced dieback and impending tree death.…”
Section: Discussionmentioning
confidence: 99%
“…Also, studies on grassland plants (both legume and grass species) found increasing root biomass production in shallow soil depths (0-15 cm) in response to drought (e.g., Prechsl et al, 2015). Moreover, shifting to shallower water uptake depths during drought might actually be beneficial for nutrient acquisition (Querejeta et al, 2021), since not only concentrations of soil water and atmospheric N2 are higher in the top soil than in the deeper soil, but also litter inputs for N mineralisation. Although we did not investigate root distributions for either crop species, they most likely follow such evolutionary strategies as well, in addition to recent crop breeding efforts leading to less deep root systems in general (Canadell et al, 1996;Thorup-Kristensen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Soil alkali hydrolyzable nitrogen and SOC mainly come from the microbial decomposition of plant litter and animal carcasses, while the SAP mainly comes from the wind erosion and desertification of soil, so the nutrients show decreasing trends with soil depth (Goebes et al, 2019;Zhang et al, 2019b;Guo et al, 2020). Precipitation can carry nutrients from the surface layer into the subsoil (Querejeta et al, 2021). However, in most of the sampling sites, MAP was lower than 60 mm and showed no significant relationship with soil nutrients across the soil profile, indicating that lower precipitation might not affect soil nutrients.…”
Section: Effects Of Mean Annual Precipitation and Soil Water Content On Soil Nutrients At Different Depths Of The Soil Profilementioning
confidence: 99%